PENERAPAN METODE SQ3R DALAM PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA - Wahyudi, Wahyudi; Halidjah, Siti; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research intended to describe the application of survey, question, read, recite, and review methods in thematic learning to improve reading comprehension skills. This research is a class action research. The study was carried out in class V of the LKIA Pontinanak Selatan Primary School, with research subjects as teachers and students totaling 18 people. Data collection techniques are observation sheets and document observing sheets of students reading comprehension results. The results of the study Survey, Question, Read, Recite, Review methods in reading comprehension obtained the results of the process of designing learning cycle I 63.52, cycle II 75.88, and cycle III 78.88, an increase of 15.36. the process of implementing learning the first cycle 71.11, second cycle 78.33 and third cycle 81.11, increased by 10. The average value of students in reading comprehension that is the first cycle 65.55, second cycle 73.33 and the second cycle III 80.00 experienced an increase of 14.45. Based on the data obtained, it was concluded that there was an increase in each cycle. This means that research by applying the Survey, Question, Read, Recite, Review methods in thematic learning in class V LKIA Pontianak Selatan Primary School can improve students' reading comprehension skillsKeywords :Comprehension, Reading, SQ3R